Military Unmanned Systems: Current State, Prospects for Limitation and Control - M. G. Yevtodyeva; S. K. Oznobishchev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines different types of modern military unmanned systems — unmanned aerial vehicles (UAVs), unmanned ground systems and unmanned maritime systems — in terms of related R&D in different countries, changes in world market demand as well as opportunities and prospects for their limitation and control. The authors provide an updated classification of these three types of unmanned systems. Based on the analysis of contemporary R&D projects and procurement data the paper shows that global market of unmanned systems will grow in the near future and that this will become a major impediment for promoting control and limitation of such systems. It is therefore equally difficult to expect expansion and strengthening of effective export control of the unmanned systems. On the contrary, opposite trends are likely to prevail, including, among all, artificial adjustment of the unmanned systems to the categories of export products with relaxed requirements. The authors conclude that it would be equally difficult to overcome other drawbacks of export control regimes, such as possibilities of non-material technology transfer or nonadherence to corresponding restrictive regimes of countries which are the largest producers and exporters of unmanned systems.Concerning UAVs’ limitation and control, the authors outline two main tracks of debate at the international level — the UN discussions on restriction of use of the unmanned platforms classified as lethal autonomous weapon systems (LAWS) and less institutionalized discussions on prospects for incorporating of unmanned systems in the set of arms control agreements.The authors identify main barriers to providing effective control over the development of the military UAVs, as well as prospects for advancement in that direction, and, finally, formulate some policy relevant recommendations.